New developments in the measurement of welfare and well-being - van Praag, Bernard M.S.; Plug, Erik J.S. (Amsterdam, 2012)
"This paper is dating from 1995, when it has been presented at the Ragnar Frisch Centennial Memorial Conference in Oslo. It has never been published before. In this paper for the first time the Cantril ladder question data have been employed in the way which later has become known as happiness economics. After two introductory sections 1and 2, Section 3 explains the Leyden School methodology to estimate financial satisfaction or in traditional terms a (cardinal) welfare function of money. In Section 4 the Cantril ladder question is employed to estimate a function of satisfaction with life as a whole. It is found that well-being is quadratic in the number of children, leading to an optimum number of children, given income and given the fact of a one-breadwinner- or two- breadwinners-family. In Section 5 the effects of children on financial satisfaction and on satisfaction with life as a whole are compared. With respect to financial satisfaction it is found that the more children there are the smaller financial satisfaction. Comparison of the two effects makes it possible to distinguish between the monetary cost associated with having children and the non-monetary benefits caused by having children. Part of this paper is based on Plug and Van Praag (1995)."